2013
DOI: 10.4103/0028-3886.115067
|View full text |Cite
|
Sign up to set email alerts
|

Unruptured intracranial aneurysms: Comparison of perioperative complications, discharge disposition, outcome, and effect of calcification, between clipping and coiling: A single institution experience

Abstract: With appropriate patient selection, the majority of the UIAs can be managed by either of the treatment modalities with very low mortality and morbidity. Both the treatment modalities should be employed synergistically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In total, 5423 articles were screened, of which 114 articles met the eligibility criteria for this review (eFigure 1 and eTables 2-4 in the Supplement). For EVT, we included 74 studies that included 71 819 patients with 73 066 aneurysms (eTable 3 in the Supplement) and for NST, we included 54 studies with a total of 34 614 patients with 35 197 aneurysms (eTable 4 in the Supplement). Fourteen of 114 studies (12.3%), with a tot...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 5423 articles were screened, of which 114 articles met the eligibility criteria for this review (eFigure 1 and eTables 2-4 in the Supplement). For EVT, we included 74 studies that included 71 819 patients with 73 066 aneurysms (eTable 3 in the Supplement) and for NST, we included 54 studies with a total of 34 614 patients with 35 197 aneurysms (eTable 4 in the Supplement). Fourteen of 114 studies (12.3%), with a tot...…”
Section: Resultsmentioning
confidence: 99%
“…For EVT, we included 74 studies that included 71 819 patients with 73 066 aneurysms (eTable 3 in the Supplement) and for NST, we included 54 studies with a total of 34 614 patients with 35 197 aneurysms (eTable 4 in the Supplement). Fourteen of 114 studies (12.3%), with a total of 33 676 patients, reported on both EVT and NST.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in concordance with the recently published case series reporting 0.0–1.6% mortality and 6.2–9.4% morbidity for unruptured aneurysm clipping. [ 13 14 15 ] In their recent review, Bacigaluppi et al . reported that a comprehensive intraoperative monitoring during aneurysm surgery reduces ischemia-related morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-operative premature rupturing is always a concern even at the hands of experienced neurovascular surgeons. [ 8 15 ] Such a mishap may lead to a catastrophe in endonasal corridor as the intense bleeding obscures the view and securing a proximal control is very difficult if not impossible. Furthermore, current endoscopes do not provide surgeons with enough magnification to do microdissection around the aneurysm whilst it is an absolute necessity to dissect the perforators off the neck.…”
Section: Discussionmentioning
confidence: 99%
“…However, since surgeons have readily adopted new endovascular techniques, enthusiasm for a trial studying unruptured aneurysms has been limited. Prior national retrospective studies 1,2,47,9,11,12,1518,20,21,24,2729,32,33,37,38 have inconclusive results and methodological limitations, with most authors failing to appropriately adjust for measured or unmeasured confounders.…”
mentioning
confidence: 99%